HABITAT PREFERENCE OF GREY FRANCOLIN (FRANCOLINUS PONDICERIANUS) IN SALT RANGE, PUNJAB - S. Khalil; M. Anwar (Journal of Animal and Plant Sciences, 2016)
The present study was conducted in two protected areas of the Salt Range i.e. Chumbi Surla Wildlife Sanctuary (CSWS) and Diljabba Domeli Game Reserve (DDGR) to generate information about preferred habitat of Grey francolin, a medium size game bird, also serving as biological control operator. Four habitat types were selected and compared for the habitat analysis study. Through vegetation survey, forty three plant species were recorded from study area, including; nine trees, six shrubs, sixteen herbs, nine grasses and three agriculture crops. In addition to this, other variables such as altitude, slope, aspect and water availability were also considered for habitat preference by Grey francolin. In CSWS, Grey francolin showed high preference for the habitat having Ivelve’s value (IV) of 0.26, while in DDGR, high preference was shown for the habitat having Ivelve’s value 0.19. Habitat-II having high elevation and aspect ranges with steep slope and having water with higher IVI for trees, seems to be the most important component for the Grey francolin to select this habitat in the entire four habitats in both CSWS and DDGR. Results would help in conservation of Grey francolin in the Salt Range.
Keywords: Grey francolin; Preferred Habitat; Salt Range; Protected area